Pengaruh Model Pembelajaran Talking Stick terhadap Hasil Belajar Kognitif Matematika Siswa SMP - Abidin, Zainal (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2023)
This study aims to determine the effect of the Talking Stick learning model on students' cognitive learning outcomes in Mathematics at Keruak 3 Public Middle School, Sepit Village, Keruak District, East Lombok Regency, 2022/2023 Academic Year. The type of research used is Quasi Experiment. The sampling technique used was the saturated sample technique, where the samples in this study were in two classes, namely the experimental class of 30 students and the control class of 30 students. Data collection techniques for students' cognitive learning outcomes were obtained using test instruments in the description. The data obtained using the t test with a significance level of 5%. The results showed that the X2count value was 2.1614 > X2table 11,070, so it can be concluded that there is an influence of the Talking Stick learning model on the cognitive learning outcomes of students at SMP Negeri 3 Keruak in the 2022/2023 academic year.